2012
DOI: 10.1089/gtmb.2012.0181
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Polymorphisms in Interleukin-10, Interleukin-6, and Interleukin-1 Receptor Antagonist in Mexican-Mestizo Women with Pre-eclampsia

Abstract: Due to the fact that studies seeking associations of polymorphisms in regulatory regions of cytokine genes with pre-eclampsia (PE) have not always been consistent in different population analyses, the aim of this study was to investigate the possible association between rs1800896 of interleukin-10 (IL-10), rs1800795 of interleukin-6 (IL-6), and the variable number of tandem repeats (VNTR) in intron 2 of interleukin-1 receptor antagonist (IL-1Ra), as well as gene-gene interactions between these three polymorphi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 30 publications
(67 reference statements)
1
15
0
Order By: Relevance
“…In addition, Pissetti et al (2014) and Vural et al (2010) carried out an investigation involving expectant women in Turkey and Brazil, revealing that the IL-10 -1082A/G sequence variant is associated with preeclampsia susceptibility. However, Valencia Villalvazo et al (2012) and Stonek et al (2008) failed to detect a correlation between this condition and polymorphisms in IL-6 and IL-10. In the present study, we identified a significant relationship between the IL-10 -592A/C variant and risk of developing preeclampsia among pregnant women in China.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…In addition, Pissetti et al (2014) and Vural et al (2010) carried out an investigation involving expectant women in Turkey and Brazil, revealing that the IL-10 -1082A/G sequence variant is associated with preeclampsia susceptibility. However, Valencia Villalvazo et al (2012) and Stonek et al (2008) failed to detect a correlation between this condition and polymorphisms in IL-6 and IL-10. In the present study, we identified a significant relationship between the IL-10 -592A/C variant and risk of developing preeclampsia among pregnant women in China.…”
Section: Discussionmentioning
confidence: 89%
“…Previous investigations have tested the association between IL-10 gene polymorphisms and preeclampsia development, but with conflicting results (Stonek et al, 2008;Vural et al, 2010;Valencia Villalvazo et al, 2012;Pissetti et al, 2014;Sowmya et al, 2014;Song and Zhong, 2015;Liu et al, 2015). Liu et al (2015) and Sowmya et al (2014) reported the IL-10 -819T/C genetic variant to be associated with increased preeclampsia risk in pregnant women in China and India.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Faisel et al studied on 133 PE patients and 112 controls from Finland, suggesting an association between the variable copy number of 86-bp tandem repeats (VNTR) of the IL1RN polymorphism and PE32. However, Valencia et al did not find the associations between polymorphism of IL1RN VNTR and PE in Mexican-Mestizo and Maya-Mestizo women33. And polymorphism of rs16944 and rs1143634 in IL-1β showed no associations with the risk of PE in Taiwanese34.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of the variable number of tandem repeats (VNTR) in intron 2 of IL‐1Ra gene remains controversial; although an Iranian study indicated the protective role of VNTR polymorphism, a study in 1024 Mexican women did not found any significant association . Moreover, a Brazilian study that explored the role of single nucleotide polymorphisms (SNPs) in IL‐1β concluded that the incidence of TC and TT genotype in rs1143630 was significantly higher in PE women .…”
Section: Resultsmentioning
confidence: 99%